2018
DOI: 10.1017/jog.2018.94
|View full text |Cite
|
Sign up to set email alerts
|

Glacier surges in the north-west West Kunlun Shan inferred from 1972 to 2017 Landsat imagery

Abstract: The West Kunlun Shan lie close to, or are perhaps part of, two significant glaciological phenomena – the High Mountain Asia surge ‘supercluster’ and the Karakoram Anomaly. However, glaciological studies, and particularly surge studies, in the range are limited. Here, we extend the database of known surges in the region using Landsat imagery and cross-correlation feature tracking. We examine 88 glaciers larger than 1 km2in the Hotan Prefecture of Xinjiang, China, and find evidence of nine surges occurring betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 70 publications
4
35
0
1
Order By: Relevance
“…Many terminus advances and changes in velocity may also be ascribed to glacier surges. The phenomenon is uncommon elsewhere in High Mountain Asia but is widespread in the Karakoram 16 and the nearby regions 31,39,40 . It has been suggested that this clustering of surge-type glaciers might be related to particular climatic and geometric conditions that lead to periodic enthalpy imbalances 18 , but the specific controls on surging remain unclear.…”
Section: Manifestations Of the Karakoram Anomalymentioning
confidence: 99%
See 1 more Smart Citation
“…Many terminus advances and changes in velocity may also be ascribed to glacier surges. The phenomenon is uncommon elsewhere in High Mountain Asia but is widespread in the Karakoram 16 and the nearby regions 31,39,40 . It has been suggested that this clustering of surge-type glaciers might be related to particular climatic and geometric conditions that lead to periodic enthalpy imbalances 18 , but the specific controls on surging remain unclear.…”
Section: Manifestations Of the Karakoram Anomalymentioning
confidence: 99%
“…This is also because data on englacial and subglacial conditions, understood to be pivotal in controlling surge cycles (Box 2), are lacking almost entirely 16 . The frequency of surge events seems to have increased in recent decades 20 , potentially correlating with a period of warming atmospheric temperatures 40 and increasing precipitations 20 . No definitive connection between surge activity and changes in external forcing has however been established yet 41 , and it is still difficult to discern whether the reported increase in surge frequency is related to a real environmental trend, or to an improved ability to detect surges through advances in observational techniques.…”
Section: Manifestations Of the Karakoram Anomalymentioning
confidence: 99%
“…High Mountain Asia (HMA) hosts the largest glacier concentration outside the polar regions. In HMA, some glaciers surging in the Karakoram and West Kunlun regions have been identified by satellite remote sensing (Copland and others, 2011; Yasuda and Furuya, 2013, 2015; Quincey and others, 2015; Bhambri and others, 2017; Usman and Furuya, 2018; Chudley and Willis, 2019), but comprehensive study of surge behaviors in this area is still limited. In this letter, by utilizing remote-sensing data, we are able to estimate and present the changes in surface velocity, terminus, morphological features and glacier thickness of Alakesayi Glacier during its recent surge and thus expand the knowledge of Alakesayi Glacier surge dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…After correlating all the selected image pairs, we first identified and removed mismatches or outliers by setting a threshold of signal-to-noise ratio (SNR), which is the ratio between the correlation maximum and the average value in the search window [36]. We chose a threshold of 5 to ensure that most of the suspicious matches could be eliminated while the more reliable estimates were reserved [22,37]. Then, all the velocity fields in the same periods were merged using a median filter both in a spatial and temporal neighborhood, for each x and y component of the velocity.…”
Section: Spatiotemporal Median Filtering and Uncertainty Assessmentmentioning
confidence: 99%